Khotbah Yang Efektif Bagi Generasi Milenial Di Era Post Modern - Jefri Hina Remi Katu (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2021)
AbstractPreaching to the millennial generation has its own challenges where this generation often known as instant generation and fast-paced that is influenced by postmodern culture. This generation also does not want to listen a lecturer or sermon that seems to long-winded. The literature analysis on this article can provide insight regarding the characteristics of the millennial generation as the audience of the message that being preached. This article describe the characteristics of the the millennial generation that become a reference in an effective preaching. An effective preaching to the millennial generation is throught the strategies of the preachers that the duration of his/her sermon is not too long, concise, and clear. And then, the selection of slangs diction of the millennial generation are required.AbstrakBerkhotbah kepada generasi milenial memiliki tantangan tersendiri di mana generasi ini kerap dikenal sebagai generasi yang instan yang serba cepat yang dipengaruhi oleh budaya postmodern dan tidak mau mendengarkan suatu ceramah atau khotbah yang terkesan bertele-tele. Pendekatan kajian pustaka dalam artikel ini dapat memberikan wawasan terkait karakteristik generasi milenial sebagai pendengar berita firman yang dikhotbahkan. Artikel ini memaparkan karakteristik generasi milenial yang menjadi acuan dalam strategi penyampaian khotbah yang efektif. Sebuah khotbah yang efektif kepada generasi milenial adalah melalui strategi-strategi dari para pengkhotbah yang durasi khotbahnya tidak terlalu lama dan bertele-tele, singkat, dan jelas. Kemudian, pemilihan bahasa-bahasa ‘gaul’ generasi milenial disyaratkan.